Effects of remedial reading and mathematics courses on educational achievement and inequities during - Hevia de la Jara, Felipe José; Vergara-Lope Tristán, Samana (IE Revista de Investigación Educativa de la REDIECH, 2022)
School closures resulting from the Covid-19 pandemic represent the most significant educational emergency of the 21st century. International recommendations include the implementation of remedial courses to address this educational emergency. The objective is to analyze the effectiveness of remedial courses using the Teaching at the Right Level (TaRL) methodology in 1) fundamental learning in reading and mathematics and 2) addressing the educational inequalities that the Covid pandemic has caused in the Mexican educational system. Methodology: A total of 360 subjects with an average age of 9.49 years from a purposive sample in Veracruz, Mexico, participated. We underwent face-to-face and online interventions, and pre-post measurements were taken to evaluate the intervention. Results: Positive and significant learning gains were identified in the participants who received the courses: 0.54 SD in Reading and 0.34 SD in Mathematics. The TaRL remedial courses helped to little reduce in gender, socioeconomic, locality, and disability gaps. The need to implement evidence-based courses to strengthen basic learning to accelerate learning and reduce educational inequalities, which increased significantly with the pandemic, is discussed, and a future research agenda is proposed.